Georgia : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of a Performance Criterion-Staff Paper; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Georgia. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Fifth Review Under the Poverty Reduction and Growth Facility for Georgia. Despite economic sanctions imposed by Russia in 2006, Georgia's economic growth continues to be strong, and inflation has declined. Growth is expected to reach 9 percent in 2006 and to slow only moderately to 7-8 percent in 2007. Inflation was back into single digits by end-2006. The 2007 budget is an appropriate compromise between the country's pressing spending needs and the goal of macroeconomic stability.